VALUABLE RELATIONSHIP BETWEEN MARITIME STUDENTS AND THE SEA: PHENOMENOLOGICAL OUTLINES - Lileikis, Saulius (Acta Paedagogica Vilnensia, 2010)
Lithuania is a maritime state. Maritime culture takes an important place in a value system of universal education from the point of view of axiology. Moral education is a part of full development of a personality. The marine education has a perspective potential of the enrichment of values to the person. This educative relationship between personality and the sea creates the context of possibilities. A process, condition and result of enrichment of values to the person are recognized by the relationship in the marine environment. Research object is valuable relationship between a person and the sea. The research aims at the exploration and evaluation of the express of the valuable relationship between youth and the sea. The aim of the article is the development of phenomenological outlines of the valuable relationship between maritime students and the sea. International Convention on Standards of Training, Certification and Watchkeeping for Seafarers, 1978, as amended in 1995 and 1997 (STCW Convention) and Seafarer’s Training, Certification and Watchkeeping Code (STCW Code), theistic humanism, existentialism and phenomenology create the epistemological basis of the research. Phenomenological outlines are revealed as tendencies of the valuable relationship between maritime students and the sea. The cognitive relationship of students at sea expresses their thoughts about home, social isolation, maturing and the sense of life. The stay near the sea expresses the recognition of relaxation, aesthetic environment, working at sea, transcendence above the trivial round, and self-development. The emotional relationship of students at sea expresses: their fear, loneliness and nostalgia for home. The stay near the sea expresses experiences of relaxation, peace and positive feeling. The relationship of aspirations of students at sea expresses the seafarer’s career, life planning and decisions to improve their personal and professional features. Very strong marine aspirations of maritime students express the seafarers’ career, which is important for their families. Students need to see life and know different ethno-cultures. Maritime lifestyle of students mostly expresses hard responsible work, the praxis to release money from the pay for work at sea, virile behavior, important social activity, travel dynamism and development of family traditions of seafarer’s.
Keywords: the valuable relationship between person and the sea; maritime students; phenomenology